Protective effect of taurine on cellular structures in rat hippocampus following ethanol intoxication. - Danielyan, M. H.; Khachatryan, V. P.; Savayan, A. A.; Nazaryan, O. H.; Karapetyan, K. V.; Sarkissian, J. S. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. Distinct brain structures, in particular, the hippocampus, have a selective sensitivity to acute and chronic alcohol intoxication. Study of the pathogenesis of alcohol-related brain damage with a view to the development of methods of prevention and treatment is an urgent task.Objective.Our main interest was in elucidating the effects of the biologically active substance, such as taurine on cellular structures in the hippocampus following ethanol intoxication.Methods.We applied a histochemical method to estimate the Ca2 + -dependent acid phosphatase activity. The present study was carried out in female albino rats. All experimental animals received an ethanol (15%) diet as their sole source of fluid at various time points.To study the effect of taurine on cellular structures of the rat brain following short-term and chronic alcohol consumption, rats were given daily injections of taurine solution for 7 days. Results. The morphological picture of the hippocampus is characterized by swelling of granular cells in the dentate gyrus that undergo chromatolysis, as well as a decrease in numerical density and a weak expression of processes of pyramidal neurons in the early stages of alcohol consumption. Degenerative changes occur in pyramidal cells in the hippocampus in the middle periods of alcohol consumption. The density of neurons is decreased; pyramidal cells lose their characteristic shape. In the conditions of long-term alcohol consumption, not only changes in the size and number of pyramidal neurons but also in the volume of the hippocampus and its regions are observed. The morphological picture of hippocampal neurons is a morphological proof of the disorders of their metabolism. In rats treated with taurine, there are positive changes in the structural properties of neurons and an increase in phosphatase activity (increased metabolism) in the hippocampus, which determines cell survival and functional recovery of irritated neurons. Conclusion. The results indicate that taurine has a neuroprotective effect on cellular structures in rat hippocampus.